Intervention Programme for Adult Victims of Childhood Sexual Abuse - Igartua Escobar, Estefanía (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2022)
The present article poses an intervention proposal for adults who have suffered of sexual abuse in their childhood and have not had the opportunity to receive psychological support. The main objective is to reduce the psychological and physical symptoms derived from such traumatic events. People who have undergone such situations often show significant deficits in managing their own emotions. Moreover, among other negative effects, they are prone to anxiety and depression, situations that can qualitatively affect both their personality and their emotions in a significant way. ln the literature consulted there are not many initiatives that offer an understanding of the problem and, at the same time, provide resources for a solid intervention with this specific population. Herein lies the novelty and practical dimension of this work, conceived simultaneously from a global and a particular perspective, so that it can be applied and adapted to diverse situations. Firstly, the problem is described. Secondly, the objectives are defined. Thirdly, a litreview is done. Fourthly, the programme is methodologically described in eight activities, together with a rational budget and evaluation criteria. Ultimately, it is expected that this programme performance will reduce the psychological and physical symptoms derived from childhood abuse in adulthood and promote a better self-knowledge and autonomy in the participants, thus reducing feelings of shame and guilt while optimizing their interpersonal relationships.